2016
DOI: 10.1038/npjmgrav.2016.30
|View full text |Cite
|
Sign up to set email alerts
|

The gravity-induced re-localization of auxin efflux carrier CsPIN1 in cucumber seedlings: spaceflight experiments for immunohistochemical microscopy

Abstract: Reorientation of cucumber seedlings induces re-localization of CsPIN1 auxin efflux carriers in endodermal cells of the transition zone between hypocotyl and roots. This study examined whether the re-localization of CsPIN1 was due to the graviresponse. Immunohistochemical analysis indicated that, when cucumber seedlings were grown entirely under microgravity conditions in space, CsPIN1 in endodermal cells was mainly localized to the cell side parallel to the minor axis of the elliptic cross-section of the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 22 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…Taken together, the present results imply that the auxin polar transport system may be constructed and function normally even in shoots grown in microgravity conditions, which may contribute to the observed maintenance of auxin levels (Table ). On the other hand, Yamazaki et al () reported that microgravity environment modified the localization of PIN proteins in endodermal cells of the transition zone between hypocotyl and root of cucumber seedlings, although it did not affect the number of endodermal cells expressing PIN proteins. These findings imply that microgravity affects the direction and/or region of auxin transported in plant stems, but not the net amount of auxin transported.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, the present results imply that the auxin polar transport system may be constructed and function normally even in shoots grown in microgravity conditions, which may contribute to the observed maintenance of auxin levels (Table ). On the other hand, Yamazaki et al () reported that microgravity environment modified the localization of PIN proteins in endodermal cells of the transition zone between hypocotyl and root of cucumber seedlings, although it did not affect the number of endodermal cells expressing PIN proteins. These findings imply that microgravity affects the direction and/or region of auxin transported in plant stems, but not the net amount of auxin transported.…”
Section: Resultsmentioning
confidence: 99%
“… 21 Currently, we know that microgravity influences auxin distribution and auxin transport in several plant species. 22 We aim to test mycorrhization in wild-type plants and mutants for SL transport or synthesis under simulated microgravity conditions, and thus investigate not only the physical influence of microgravity on this plant-fungal symbiosis, but also to assay the efficiency of SL as a tool to promote mycorrhization under microgravity conditions. These results will establish and enhance our knowledge of mycorrhization in space and show that mycorrhiza could be a feasible and smart tool to increase plant adaptability and yield also in extraterrestrial environments.…”
Section: Introductionmentioning
confidence: 99%
“…AtLAZY1 likely functions in close association with auxin transport by regulating the re‐localization of PIN‐FORMED (PIN) protein on the plasma membrane (Taniguchi et al , Yoshihara and Spalding ). Although the regulatory mechanism is still unknown, some PIN proteins in gravisensing cells re‐localize in response to gravity, which leads to asymmetric auxin transport and distribution, thereby mediating the graviresponse (Friml et al , Kleine‐Vehn et al , Rakusová et al , Yamazaki et al ). It is therefore likely that LAZY1 is responsible for circumnutation through mediating the regulation of the gravity response via its effects on auxin transport.…”
Section: Discussionmentioning
confidence: 99%